Random mutagenesis of 1-aminocyclopropane-1-carboxylate synthase: A key enzyme in ethylene biosynthesis - Tarun, Alice S. (National Academy of Sciences, 1998)
1-Aminocyclopropane-1-carboxylate synthase (ACC synthase, EC 4.4.1.14) catalyzes the rate-limiting step in the ethylene biosynthetic pathway in plants. To determine the amino acid residues critical for the structure and function of this enzyme, the tomato Le-ACS2 isoenzyme has been subjected to both site-directed and PCR random mutagenesis. Mutant ACC synthases with reduced enzyme activity have been selected by using a genetic screen based on the functional complementation of an Escherichia coli Ile auxotroph that has been engineered to express ACC deaminase from Pseudomonas sp. The DNA sequence of almost 1,000 clones has been determined, and 334 single missense mutations have been selected for analysis. We have identified three classes of mutants based on their activity and expression in E. coli. Class I and II mutants have the same level of protein expression as the wild type, but their enzyme activity is reduced to 0–5% and 5–50%, respectively. Class III mutants have neither activity nor detectable protein expression. The inactive mutations are clustered in regions that are highly conserved among various ACC synthases. This library of mutants will facilitate the elucidation of structure-function relationships of this regulatory enzyme.